Age and Sex Related Variations in Haemoglobin Level - Hathnagoda Hemrtk; Edirisinghe Dpt; Rathnayaka Hgnt; Baragamaarachchi Ry (American Scientific Research Journal for Engineering, Technology, and Sciences, 2022)
Haemoglobin (Hb) is the functional protein in Red Blood Cells, which mainly involve in transportation of Oxygen from lungs to peripheral tissues. The objective of this study is to analyse the age and sex specific variations of haemoglobin level in a group of individuals. The study was conducted at Ceymed Healthcare Services laboratories, Nugegoda, where data from full blood count reports of 100 individuals were collected for 5 consecutive days. Among the 100 individuals, 51 were males and 49 were females. The analysed data showed that the average Hb level was 12.27 ± 2.05 g/dL (mean ± SD). It was lower in females; 11.73 ± 1.51 g/dL (mean ± SD) than in males; 12.79 ± 2.37 g/dL (mean ± SD). Most of the individuals in the sample we collected were males.  Haemoglobin level of 45% of individuals were within the normal range while 54%, had low haemoglobin levels. Also 1% of high hemoglobin individuals were found. Most of the anaemic males belonged to the age group 60-70, whereas most female anemic patients belonged to the age group 30-39. Prevalence of anemia in the studied population was equal among both sexes. The new findings of this study showed the distribution of Hb levels relate to age and gender.